Molecular detection of Hepatozoon species infections in domestic cats living in Germany. Issue 10 (October 2022) - Schäfer, Ingo; Kohn, Barbara; Nijhof, Ard M; Müller, Elisabeth
Objectives: Three species of protozoal Hepatozoon species ( H felis, H canis and H silvestris ) are known to infect cats in Europe. The objective of this study was to determine the prevalence of Hepatozoon species in samples from cats living in Germany that were submitted to a veterinary laboratory. Methods: The study included cats tested for Hepatozoon species by PCR between 2007 and 2020 by the Laboklin laboratory. Travel history and haematological results were documented for cats with positive test results. From 2018 onwards, a partial 18S rRNA Hepatozoon gene fragment was sequenced from cats with positive PCR results. Results: Sixty-four of 931 cats (7%) tested positive for Hepatozoon species. Sex and age did not have a statistically significant impact. Sequencing was carried out for 16 samples and revealed H felis in all cases. All cats with positive test results and a relevant travel history had been imported from the Mediterranean or south-eastern Europe. There were no autochthonous infections with Hepatozoon species. Leukocytosis, haemoconcentration and anaemia were the most common haematological abnormalities. Conclusions and relevance: Although infections with Hepatozoon species in cats are usually subclinical, it may be useful to screen cats imported from the Mediterranean and south-eastern Europe for these pathogens to prevent local transmission cycles. There was no evidence of autochthonous infections in Germany; however, further investigations regarding a possible transmission of Hepatozoon species from infected cats to blood-feeding arthropods in Germany may be of interest. To avoid potential spread of the pathogens, ectoparasite prophylaxis is advisable.